1997
DOI: 10.1002/bjs.1800840211
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the contractile properties of colonic smooth muscle in idiopathic slow transit constipation

Abstract: These findings indicate that colonic smooth muscle from patients with ISTC is hypersensitive to cholinergic stimulation and suggest the existence of a smooth muscle myopathy in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Hypersensitivity to cholinergic stimulation has previously been demonstrated in colonic smooth muscle from patients with idiopathic slow transit constipation and it was suggested that this might be explained by the development of a secondary denervation hypersensitivity 18 . This explanation is in keeping with abnormalities known to exist in the myenteric plexus of these patients and supported by the finding of a functional cholinergic deficit in response to electrical stimulation of the myenteric plexus 19 , .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Hypersensitivity to cholinergic stimulation has previously been demonstrated in colonic smooth muscle from patients with idiopathic slow transit constipation and it was suggested that this might be explained by the development of a secondary denervation hypersensitivity 18 . This explanation is in keeping with abnormalities known to exist in the myenteric plexus of these patients and supported by the finding of a functional cholinergic deficit in response to electrical stimulation of the myenteric plexus 19 , .…”
Section: Discussionmentioning
confidence: 66%
“…Organ bath experiments are a robust and well established means of assessing smooth muscle function 16 –18 . Contractile responses of rectal smooth muscle to carbachol and potassium are well recognized and similar responses to each were observed in both ulcerative colitis and cancer strips.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is also supported by physiological data in-vivo where ambulatory 24 hour colonic manometry showed features suggestive of a myopathy in 24% of select patients with STC [84]. It is supported by some in-vitro data from organ bath studies of colonic muscle strips from patients with constipation [78, 83] but not by others [85]. Despite this, there is remarkably little known about myopathies in chronic idiopathic constipation and slow transit constipation at a tissue level.…”
Section: Myopathymentioning
confidence: 67%
“…There are several reports of significantly decreased [46, 50,81,82]; or increased [49] immunohistochemical densities of nerve structures (variably described as nerve fibres, enteric neurofilaments and small axonal fibres) as determined by subjective or automated counting methods. While these changes may have potential pathophysiological importance [83], aside from the contradictory nature of findings, there are no current standardized methods or robust normative data to render diagnostic utility to such measurements.…”
Section: Neuropathymentioning
confidence: 99%
“…Most myopathies are characterized by intestinal dilatation (pseudo‐obstruction), although some patients present with constipation. Consistent findings have not been demonstrated by light microscopy in patients with STC5, 6, and in vitro physiological studies have produced conflicting results11, 12. Morphological changes seen in intestinal myopathies include varying degrees of fibrosis, hypertrophy or atrophy of muscle fibres, vacuolation of myocytes9, 13, 14, alteration in the immunohistochemical staining patterns of myocyte contractile proteins15, abnormal layering of the muscle9, and the presence of intracellular inclusion bodies14.…”
Section: Introductionmentioning
confidence: 98%